Overcoming hypoxia-induced functional suppression of NK cells. Issue 1 (28th April 2020) - Solocinski, Kristen; Padget, Michelle R; Fabian, Kellsye P; Wolfson, Benjamin; Cecchi, Fabiola; Hembrough, Todd; Benz, Stephen C; Rabizadeh, Shahrooz; Soon-Shiong, Patrick; Schlom, Jeffrey; Hodge, James W
Abstract : Background: Natural killer (NK) cells are immune cells capable of killing virally infected cells and tumor cells without the need for antigen stimulation. Tumors, however, can create a suppressive microenvironment that decreases NK function. A feature of many tumors is hypoxia (low oxygen perfusion), which has been previously shown to decrease NK function. A high affinity NK (haNK) cell has been engineered to express a high affinity CD16 receptor as well as internal interleukin (IL)-2 for increased antibody-dependent cellular cytotoxicity (ADCC) and activation, respectively. We sought to investigate the tolerance of NK cells versus haNK cells to hypoxia. Methods: We exposed healthy donor (HD) NK and X-irradiated haNK cells to normoxia (20% oxygen) as well as hypoxia (0% oxygen) and investigated their ability to kill prostate, breast and lung tumor cell lines after 5 hours. We also used monoclonal antibodies cetuximab (anti-EGFR) or avelumab (antiprogrammed death-ligand 1) to investigate the effects of hypoxia on NK ADCC. Genomic and proteomic analyzes were done to determine the effect of hypoxia on the expression of factors important to NK cell function. Results: While HD NK cell cytolytic abilities were markedly and significantly impaired under hypoxic conditions, haNK cells maintained killing capacity under hypoxic conditions. NK killing, serial killing and ADCC were maintained under hypoxia in haNK cells. IL-2 has been previously implicated in serial killing and perforin regeneration and thus the endogenous IL-2 produced by haNK cells is likely a driver of the maintained killing capacity of haNK cells under hypoxic conditions. Activation of signal transducer and activator of transcription 3 (STAT3) is not seen in haNKs under hypoxia but is significant in HD NK cells. Pharmaceutical activation of STAT3 in haNKs led to reduced killing, implicating active STAT3 in reduced NK cell function. Conclusions: In contrast to HD NK cells, haNK cells are resistant to acute hypoxia. The potent cytolytic function of haNK cells was maintained in an environment comparable to what would be encountered in a tumor. The data presented here provide an additional mechanism of action for haNK cells that are currently being evaluated in clinical trials for several tumor types.